Pengaruh Leverage, Arus Kas Operasi, dan Capital Intensity terhadap Financial Distress - Sabrina Nurhaliza; Etty Gurendrawati; Diah Armeliza (LPPM Universitas Negeri Jakarta, 2026)
This research examines the effects of leverage, operating cash flow, and capital intensity on financial distress in property and real estate companies listed on the Indonesia Stock Exchange during 2022–2024. Financial distress is measured using the modified Altman Z-Score for emerging markets. The sample was selected through purposive sampling, and the data were analyzed using panel regression with the random effect model. The results indicate that leverage and capital intensity positively influence financial distress, whereas operating cash flow negatively influences financial distress. These findings support the trade-off theory, suggesting that effective debt management, strong operating cash flow, and appropriate investment in fixed assets are important for maintaining a company’s financial stability and reducing the risk of financial distress.